HUBUNGAN STRATEGI KOPING DENGAN KECEMASAN UJIAN DALAM MENGHADAPI OSCE PADA MAHASISWA PSIK UGM - , LATIFAH SIDHI ADNANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
OSCE (Objective Structured Clinical Examination) to be one of the components of the block 4.5 CCNS assessment (Comprehensive Clinical Nursing Skills) with a percentage rating of 70%. CCNS OSCE considered to be the test that have more stressors than other exams for testing this 22 stase skills. The situation assessment skills test with a high standard, limited time, material and exams are tough competition exams cause anxiety. Test anxiety is one reason that can affect performance and graduation. One way to address and resolve the situation before and during the OSCE anxiety is by using coping strategies. Objective: To determine the relationship between coping strategies with PSIK GMU student test anxiety at the time of the OSCE. Methods: A cross-sectional study conducted on 92 students of 4th year PSIK GMU in May during the OSCE block 4.5. The instrument used in the form of German Test Anxiety Inventory (TAI-G) test to measure anxiety and Coping Strategy Indicator (CSI) to measure coping strategies. Results: No significant correlation (p> 0.05) between test anxiety coping strategies with the students of the Faculty PSIK in the OSCE. Coping strategies used by the respondent (4th year student PSIK UGM) is a problem solving coping number of 51 students (55.4%), seeking social support coping as many as 39 (42.4%) and who choose avoidance coping by 2 students (2 , 2%). Moderate level of test anxiety is mostly experienced by 4th years students of PSIK UGM.